2014
DOI: 10.4028/www.scientific.net/amm.580-583.636
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Analysis and Safety Evaluation of Deep Foundation Pit under Complex Conditions

Abstract: The horizontal displacement of pit top and horizontal displacement in deep soil of underground garage deep foundation pit in Radio and TV centre of Shandong province was analyzed. Combing the deformation control value of foundation pit, we thought that the supporting structure was safe and reliable. The supporting structure could not only meet the strength requirements but also meet the deformation control requirements. This deep foundation pit was a successful case under complex conditions. Analyzing the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…But establish a reasonable membership function is very difficult, need to constantly test and summary. In this paper, the determination of membership function is referenced the literature [6] , established a trapezoid and trapezium membership function. pit in safe state membership function…”
Section: Warningmentioning
confidence: 99%
“…But establish a reasonable membership function is very difficult, need to constantly test and summary. In this paper, the determination of membership function is referenced the literature [6] , established a trapezoid and trapezium membership function. pit in safe state membership function…”
Section: Warningmentioning
confidence: 99%
“…Hu et al [7] identified design and construction factors such as insufficient embedded pile depths and insufficient anchor pull-out resistance as being responsible for foundation pit accidents. Having dynamic loads around deep foundation pits is also a factor in pit collapse [8]. In addition, Xu et al [4] also identified several main risk events that can cause foundation pit accidents, including failure to follow engineering design, collapse of pit bracing structures, falling from a significant height due to a lack of edge protection, and collapse of the pit due to excavation.…”
Section: Introductionmentioning
confidence: 99%